2013
DOI: 10.1186/1475-925x-12-5
|View full text |Cite
|
Sign up to set email alerts
|

In vitro assessment of Function Graded (FG) artificial Hip joint stem in terms of bone/cement stresses: 3D Finite Element (FE) study

Abstract: BackgroundStress shielding in the cemented hip prosthesis occurs due to the mismatching in the mechanical properties of metallic stem and bone. This mismatching in properties is considered as one of the main reasons for implant loosening. Therefore, a new stem material in orthopedic surgery is still required. In the present study, 3D finite element modeling is used for evaluating the artificial hip joint stem that is made of Function Graded (FG) material in terms of joint stress distributions and stem length.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…With titanium alloy, stress of 77 MPa was obtained whereas when used CoCrMo as implant material, stress of 88 MPa was obtained. 27 Regarding stem length, the stresses increased with increase in stem length. Research is being done by many authors on the effect of neck length on implant stresses and contradictory observations are reported.…”
Section: Resultsmentioning
confidence: 97%
“…With titanium alloy, stress of 77 MPa was obtained whereas when used CoCrMo as implant material, stress of 88 MPa was obtained. 27 Regarding stem length, the stresses increased with increase in stem length. Research is being done by many authors on the effect of neck length on implant stresses and contradictory observations are reported.…”
Section: Resultsmentioning
confidence: 97%
“…All numerical results pointed toward a reduction in stress shielding. Low modulus at the distal end and high modulus at the proximal end was suggested by Al-Jassir et al [107] to improve the performance of the femoral stem. The proposed material combination was titanium alloy and cobalt chromium alloy, which may be challenging to grade together.…”
Section: Porositymentioning
confidence: 98%
“…Bahraminasab et al [55,56] investigated advantages of FGMs over other material like titanium alloys, stainless steel or cobalt chromium molybdenum (CoCrMo) and concluded that using FGMs results reduction in stress developed in the neighboring part of tibia tray. FGMs is also using in the artificial hip joint replacement [57][58][59]. Jassir et al [59] suggested that using FGMs instead of CoCrMo and Ti alloy results reduction in stress in bone cement and stem which is the main parts of total hip replacement.…”
Section: Biomedical Applicationmentioning
confidence: 99%
“…FGMs is also using in the artificial hip joint replacement [57][58][59]. Jassir et al [59] suggested that using FGMs instead of CoCrMo and Ti alloy results reduction in stress in bone cement and stem which is the main parts of total hip replacement.…”
Section: Biomedical Applicationmentioning
confidence: 99%